Orquestrando criatividade e capacidade de inteligência artificial para aumentar o desempenho em startups - Majorana, Cristina Doritta Brandão (2023)
The overall objective is to evaluate the mediation effect of artificial intelligence capability in the relationship between organizational creativity and the performance of technology-based startups. The thesis argues that when organizational creativity is orchestrated to develop tangible, intangible, and human artificial intelligence resources and to create artificial intelligence capability, the synchronism between both affects performance and reveals the total mediation effect of artificial intelligence capability. This pathway, in which organizational creativity impacts artificial intelligence capability, which in turn impacts performance, is under investigation. Therefore, by adopting the perspective of the competencies hierarchy and Resource Orchestration Theory, the research brings as a novelty the synchronization of organizational creativity with the artificial intelligence capability to generate performance in startups, whose result reveals the total mediation effect of the artificial intelligence capability, which, as far as is known, has not yet been investigated, and goes beyond the indirect effect of this capability on performance and the direct effect of this capability on organizational creativity found in previous studies. The approach is quantitative. The method is the primary data collection, collected between October 2022 and January 2023 through a survey answered by 166 managers and employees of technology-based startups operating in Brazil and international markets. Data are analyzed by multiple linear regression. Results show that artificial intelligence capability fully mediates the relationship between organizational creativity and the performance of technology-based startups. The study brings two theoretical contributions. First, the study shows that organizational creativity is a base resource activated in the structuring and bundling processes that precede the development of artificial intelligence resources and the creation of artificial intelligence capability in startups. The synchronism between both reveals the effect of total mediation of this capability. The research advances theoretically by revealing the unprecedented effect of total mediation of artificial intelligence capability and shows the intersection of organizational creativity with artificial intelligence resources in structuring the firm’s resource portfolio. Second, the study expands the understanding of asset orchestration with a focus on the life cycle of technology-based startups and shows that the phases of these companies influence performance, the development of tangible artificial intelligence resources, and the synchronization to drive performance gains. However, when analyzing the creation of artificial intelligence capability, the phase ceases to be significant. Therefore, the research shows that startups at any phase can create artificial intelligence capability if they have organizational creativity in their resource portfolio and need to be in the scalability phase to obtain performance gains from synchronism. Managerial implications, study limitations, and suggestions for future research are presented at the end.